Three new cryptogenic species in the tribes Polysiphonieae and Streblocladieae (Rhodomelaceae, Rhodophyta). Issue 6 (1st November 2017) - Díaz-Tapia, Pilar; Bárbara, Ignacio; Cremades, Javier; Verbruggen, Heroen; Maggs, Christine A.
Abstract: During our sampling surveys of the tribes Polysiphonieae and Streblocladieae in Spain and Australia, three previously unrecorded species were collected. Based on molecular and morphological evidence they are proposed as new species. Polysiphonia delicata sp. nov . and Polysiphonia radiata sp. nov . belong to the Polysiphonieae and share the synapomorphy in this group, rhizoids in open connection to pericentral cells. They differ from other members of this group either by rbc L sequence divergences greater than 4.5% and/or by morphological characters. The third species is placed in Melanothamnus (tribe Streblocladieae), as Melanothamnus pseudoforcipatus sp. nov . In agreement with the morphological delineation of the genus, it has plastids lying only on the radial walls of pericentral cells. It can be separated from most other members of the genus by having naked segments between trichoblasts or branches and/or rbc L sequence divergences higher than 4%. In Galicia, Spain, both Polysiphonia species were mainly collected in marinas, while M. pseudoforcipatus was found at a site close to oyster aquaculture facilities. Polysiphonia delicata was also found in Victoria, Australia, and the potentially non-native status of these three species in relation to their known distribution is discussed.